Digital media management training for more advanced village development in Desa Taringgul Tonggoh, Kec. Wanayasa - Adi Wijaya; Muhamad Rizky; Regina Ghaida; Bambang Erawan (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
The Wanayasa area is one of the areas in Purwakarta that has abundant natural resources, creative and innovative human resources, and also has the potential for developing villages, one of which is Taringgul Tonggoh Village which has won 3rd place in the Java Province Village and Subdistrict Competition, west in 2023. The Village Government is trying to develop lagging aspects by developing digital media management to maintain what has been achieved. Therefore, the service program in the form of Real Work Lectures (KKN) created in this paper aims to educate the Village Government by conducting Digital Media Management Training for Village Development. This training aims to provide training so that Village Officials are proficient in operating Digital Media in Taringgul Tonggoh Village, including Instagram, Facebook, and the My Village Website. In digital media, village profiles are updated, village news adds village tourism, and completed village products (food and crafts) are in marketing features. After this program is implemented, village officials can create posters for design activities, social media posts in an organized manner, and appropriate captions for the posts. Village Officials gain insight into the village website and can manage it.   Abstrak Daerah Wanayasa merupakan salah satu daerah di Purwakarta yang mempunyai sumber daya alam yang melimpah, sumber daya manusia yang kreatif dan inovasi, dan juga mempunyai potensi desa yang berkembang, salah satunya yaitu Desa Taringgul Tonggoh yang telah meraih Juara 3 Lomba Desa dan Kelurahan Tingkat Provinsi Jawa barat tahun 2023. Untuk mempertahankan dengan apa yang sudah diraih Pemerintah Desa mengupayakan untuk mengembangkan aspek yang ketertinggalan yaitu dengan mengembangkan pengelolaan media digital. Oleh sebab itu program pengabdian dalam bentuk Kuliah Kerja Nyata (KKN) yang dibuat dalam tulisan ini bertujuan untuk mengedukasi Pemerintah Desa dengan melakukan Pelatihan Pengelolaan Media Digital untuk Pengembangan Desa. Pelatihan ini bertujuan untuk memberikan pelatihan agar Perangkat Desa mahir untuk mengoprasikan Media Digital yang terdapat pada Desa Taringgul Tonggoh diantaranya Instagram, Facebook, dan Website Desaku. Dan di Media Digital itu memperbarui profil desa, pengunggahan berita desa, penambahan wisata desa, dan melengapi produk desa (baik makanan ataupun kerajinan) di fitur pemasaran. Setelah program ini dilaksanakan, Perangkat Desa dapat membuat desai poster kegiatan, membuat postingan media sosisal secara tertata, serta caption yang sesuai dengan postingan, dan Perangkat Desa mendapatkan wawasan terkait website desa dan dapat mengelola website tersebut. Kata Kunci: Pengembagan media digital; platform desa; platform digital